Central composite experimental design for the investigation of the influence of various conditions of anodisation on the amount of antimicrobial agent loaded on TiO2 nanotubes. (1st August 2015) - Lotfi, M.; Sabzi, R.E.; Bahram, M.; Samadi, N.
Abstract : TiO2 nanotubes on Ti substrate were prepared by electrochemical anodisation method. Central composite experimental design was used to design the experiments to investigate the influence of some variables on the loading of antibiotic gentamicin. A full quadratic model was used in order to find out the influence of the variables and their possible interactions and finally to estimate the optimum conditions. Titanium rods were anodised in ethylene glycol containing different amounts of ammonium fluoride and water at different voltages and different anodising times. Antibacterial activity of the nanotubes prepared under the optimum condition was evaluated by a culture test with Staphylococcus aureus bacteria.